Calculate the Attenuation of X-ray radiation for low density polyethylene composites with oyster shells powder extracted from the Caspian Sea in Iran - Mohammed, Ahmed Jassim; Ramadan, Riad Manadi; Shaban, Raed Muslim (Journal of natural sciences, life and applied sciences, 2019)
In this research, Calculation the Attenuation of X-ray radiation for low density polyethylene composites with oyster shells powder (extracted from the Caspian Sea in Iran), low density polyethylene production in the form of powder by the State Company for Petrochemical Industries (Basra-Iraq), the range of the added of oyster shells powder (extracted from the Caspian sea in Iran) has the values (0%, 2.5%, 5%, 10%, 15%, 20%, and 25%) for low density polyethylene weight and the added oyster shells powder with the particular size (≤ 250 μm). were investigated through several variables, such as, linear attenuation coefficient(μ) and mean free path(λ). The obtained results were appeared that the added oyster to reduce the spaces between the polymer chains, which reflects the high ability of the polymer as (10%-20%), and this increase will give further property that increase the attenuation x-ray of the prepared specimens. Where the practical study and the beam of intensity of energy (30 kv) and)VG.M = 600 voit(. The results showed that when increasing filler content, the total linear attenuation coefficient increases while the mean free path decreases. The mean free path (λ) at (2.5%) is (2.1 cm (, while at (20%) is (0.40 cm). The value of the linear attenuation coefficient (μ) at (20%) is)2.44 cm-1(, while at (2.5%) is) 0.49 cm-1(.
Keywords: low-density polyethylene (LDPE); fillers; oyster shell powder; x-ray; linear attenuation coefficient (μ); free path rate (λ)